Correlation Based Mechanism for the Detection of DDOS Attack - Simmi; Kaur, Harjinder (International Journal of Computer Sciences and Engineering, 2021)
As technology is blooming cloud computing becomes indispensible part of many companies. The users are dependent upon cloud infrastructure as it is widely adopted and used technology. In cloud computing the prime concern is shared storage and it has many security issues. One of these security issues is DDOS attack that can effect business organization which utilizes cloud. This paper describes an approach to handle DDOS attack in cloud systems. In the proposed approach Interpolation between the values are located. In the proposed approach, security attributes gives highest Interpolation and reliability is the next highest Interpolation values. Both of these attributes serve as root nodes. The comparison between these attributes and training data is made to determine the DDOS attack. This means complication of calculations is reduced. Execution time is greatly reduced using this procedure. Results obtained are similar but execution time is reduced. The mechanism of ordering and normalization gives the hierarchical clustering.